Double seropositive neuromyelitis optica associated with COVID-19: A case report - Antonescu Ghelmez, Dana; Moraru, Adriana; Antonescu, Florian; Chelmambet, Altay Sercan; Bucur, Amanda Ioana; Tuţǎ, Sorin (Frontiers in Neurology, 2022)
Neuromyelitis optica spectrum disorders are characterized by severe demyelination and axonal damage with autoimmune mechanisms, predominantly targeting the optic nerves and the spinal cord. Patients most often test positive for antiAQP4 antibodies, while some have anti-MOG antibodies. Double seropositivity has been described, with a variable prevalence (0 to 26%), dependent on the testing method. The clinical significance of double seropositivity is unclear. We present the case of a patient, who was admitted to our clinic with optical neuritis, followed about ten days later by cervical myelitis, who tested positive for both anti-AQP4 and anti-MOG antibodies. The clinical onset coincided with a mild form of SARS-CoV2 infection. The neurological symptoms were initially quite subdued, a fact which delayed the diagnosis. The patient was not vaccinated against COVID19. The clinical picture was compatible with an antiAQP4 phenotype. The patient was started on corticosteroids therapy, under which the clinical response was good. Our case reinforces the idea that a SARS-CoV2 infection can precipitate autoimmune demyelinating diseases, since SARS-CoV2 infection was already demonstrated as a risk factor for NMOSD relapses. To the best of our knowledge, this is the first reported case of double seropositive neuromyelitis optica post-COVID19 infection. We expect that in the near future, as the true burden of long COVID19 becomes more clear, we will encounter other cases which can trace their apparent clinical onset to a SARS-CoV2 infection. Careful attention should be paid to apparent minor neurological symptoms accompanying SARS-CoV2.